Analisis Model Antrian Loket Transaksi pada PT. POS Indonesia (persero) Kantor Cabang Sawangan dengan Menggunakan Software Promodel - Drajat Indrajaya; Riri Cornellia (Universitas Indraprasta PGRI Jakarta, 2018)
Simulation is a process of imitation of a tangible thing and its surroundings. The problem found in this study is a long queue at the payment counter resulting from numerous customers who come to POS Company. It is also caused by some factors such as a small number of cash registers, with only 2 counters functioned irregularly and less extensive queue lines. Considering that, an analysis of the queues at the payment counters using pro model software application is made to anticipate the long queues. This simulation is run for 6 hours with 10-time replication, verified and is then validated. The queue model used is (M/M/2):(FCFS/ / ), meaning the number of arrivals uses Poisson distribution and the service time uses exponential distribution. With the number of facility service as many as 2 people, the discipline used is the customer who comes first will be served first (first come first serve). The number of queues in the queue system and the size of the population at the source of arrival is infinite. The average percentage of teller utilities is 62.14% and the idle percentage of teller is 37.86%. The average number of customers completing transactions is 119.30 ? 120 customers for 6 hours. The average time spent by customers in the queue until they are served is 3.67 minutes. The average time customer spends in the system is 6.08 minutes.